2020
DOI: 10.21203/rs.3.rs-127913/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the limitations in assessing stability of oxygen evolution catalysts using aqueous model electrochemical cells

Abstract: Recent research indicates a severe discrepancy between oxygen evolution reaction (OER) catalysts dissolution in aqueous model systems and membrane electrode assemblies (MEA). This questions the relevance of the widespread aqueous testing for real world application. In this study, we aim to determine the processes responsible for the dissolution discrepancy. Experimental parameters known to diverge in both systems are individually tested for their influence on dissolution of an Ir-based catalyst. Ir dissolutio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…From the industrial application perspective, rutile-type Rurich Ir x Ru 1−x O 2 compositions would then be the optimal approach to find a cost-effective yet active OER catalyst: the metastable Ir-enriched shell would stabilize the underlying Rurich phase after long-term operation, providing a higher OER conversion rate at reasonable stabilities. Indeed, a very recent study has corroborated that electrochemical stability of OER catalysts is substantially prolonged in PEMWE systems compared to aqueous model systems, 131 which would reinforce the use of an Ir-protected active phase electrocatalyst.…”
Section: Discussionmentioning
confidence: 93%
“…From the industrial application perspective, rutile-type Rurich Ir x Ru 1−x O 2 compositions would then be the optimal approach to find a cost-effective yet active OER catalyst: the metastable Ir-enriched shell would stabilize the underlying Rurich phase after long-term operation, providing a higher OER conversion rate at reasonable stabilities. Indeed, a very recent study has corroborated that electrochemical stability of OER catalysts is substantially prolonged in PEMWE systems compared to aqueous model systems, 131 which would reinforce the use of an Ir-protected active phase electrocatalyst.…”
Section: Discussionmentioning
confidence: 93%
“…Samples were tested at constant current in the chip EC-MS setup modified to collect electrolyte samples for ICP-MS measurements of metal dissolution before post-reaction LEIS characterization. The dissolution of OER catalysts is known to be dependent on the flow characteristics of the setup 32 -in this regard, the stagnant thin layer of electrolyte in the EC-MS setup resembles more the environment experienced by an OER catalyst in a PEMEC than do most aqueous model systems.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a study provided a detailed examination between lab-scale three-electrode cells and commercial-scale electrolyzers. 141 The results indicated that IrO x are more stable in commercial-scale electrolyzers. An overestimated local acidity on the catalyst as well as stabilization processes over time in the electrolyzers have been identified as the main reasons for this difference.…”
Section: Oer Stability In Practical Electrolyzersmentioning
confidence: 96%